Growth and Hematological Response of Common Carp (Cyprinus carpio) to Dietary Supplementation with Water Hyacinth (Eichhornia crassipes) Extract - Putri, Marselia Aisyah; Cokrowati, Nunik; Setyono, Bagus Dwi Hari (Journal of Fish Health, 2025)
This study examined the effects of dietary supplementation with Eichhornia crassipes leaf extract on the growth performance and hematological parameters of common carp (Cyprinus carpio). Phytochemical screening confirmed the presence of bioactive compounds such as flavonoids, alkaloids, and saponins, with moderate antioxidant activity (50.89% DPPH inhibition). Experimental treatments showed that fish receiving moderate levels of the extract had significantly higher erythrocyte and leukocyte counts, indicating improved oxygen transport and immune function. Additionally, the group with the highest absolute weight gain suggests better nutrient absorption. All treatments maintained a 100% survival rate and stable water quality, confirming the extract’s safety and environmental compatibility. These results support the use of E. crassipes as a sustainable, cost-effective, and environmentally friendly alternative to synthetic growth promoters in aquaculture. Further research is recommended to investigate its long-term effects and mechanisms of action.